Related factor of Knowledge by Stroke in Institute of Higher Education Employees - Wardhani, Novida Rizky; Martini, Santi (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTStroke is an infectious disease cause of death was not ranked top in urban areas according Depkes (2011) approximately 28.5% of stroke patients died, the rest partially paralyzed or even paralyzed and the remaining 15% can be cured. Stroke is taking place in people who are productive. This study aims to Related factor of Knowledge by Stroke in Institute of Higher Education Employees. This study was analytical research with cross sectional design. The questionnaire given to 142 respondents. Dependent variable in this study was the knowledge about stroke risk factors, the level of knowledge of the early recognition of stroke symptoms and the knowledge how to handle. The independent variables were age, gender, and education level. Data analysis using Chi Square test and Spearman test. The results showed the level of knowledge of stroke risk factors 78.9% of respondents in the level of knowledge of "good" about stroke risk factors, the level of early recognition of stroke symptoms FAST  method from respondents largely in the category of "not good", and 63.4% of the respondents have know how to handle it properly. Results of the analysis showed significant relationships between the sexes is the level of knowledge of risk factors for stroke, p = 0.020 so that p < α (0,05). Furthermore the relationship between level of education and the level of early recognition of stroke symptoms, p = 0.006 to p < α (0.05) and the value obtained was 0,229 r. Conclusion of this research knowledge of risk factors was well, correct of treatment knowledge, correct medical stroke center was hospital, appropriate time window less of 3 hours and only level early recognition of stroke symptoms still not quite knew.Key words : risk factors, first symtomps, knowledge, stroke, employee, higher education